2017
DOI: 10.1177/2056305117698495
|View full text |Cite
|
Sign up to set email alerts
|

Differential Influences of Depression and Personality Traits on the Use of Facebook

Abstract: Depressive symptoms are highly prevalent among younger populations and have been clearly associated with lowered activity in general. Focusing on Facebook use as an extremely popular leisure activity, this study examines the influence of depressive tendencies on the intensity of using Facebook by considering the moderating effects of relevant personality traits and different motivations associated with social network site (SNS) use. Based on an online survey among 510 young Facebook users, this study shows tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…The researchers also found no significant relationship between neuroticism and Facebook addiction, thus accepting the null hypothesis. In a similar study by Scherr and Brunet (2017), findings revealed that neuroticism only influence the motivations behind Facebook usage and not directly affect the time being sent on Facebook. Furthermore, Hughes, Rowe, Batey, and Lee (2012) concluded that although it has been revealed in their study that an individual's personality was related to Facebook usage, the correlations were not direct or significant as other research suggested as other factors such as motivation behind Facebook use, self-efficacy and intelligence could be influential.…”
Section: Discussionmentioning
confidence: 84%
“…The researchers also found no significant relationship between neuroticism and Facebook addiction, thus accepting the null hypothesis. In a similar study by Scherr and Brunet (2017), findings revealed that neuroticism only influence the motivations behind Facebook usage and not directly affect the time being sent on Facebook. Furthermore, Hughes, Rowe, Batey, and Lee (2012) concluded that although it has been revealed in their study that an individual's personality was related to Facebook usage, the correlations were not direct or significant as other research suggested as other factors such as motivation behind Facebook use, self-efficacy and intelligence could be influential.…”
Section: Discussionmentioning
confidence: 84%
“…This supports previous studies that have found that those who are in a negative mood engage in activities on SNS to manage their mood (Johnson & Knobloch‐Westerwick, 2014; Sherr & Brunet, 2017). A recent study by Scherr and Brunet (2017) found that young adults who exhibited depressive tendencies used Facebook for status updating because it enabled them to have a network they could turn to during episodes of depression. Support offered through social relationships with both peers and family members may provide varied roles within the SNS environment.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers also found no significant relationship between neuroticism and Facebook addiction, thus accepting the null hypothesis. In a similar study by Scherr and Brunet (2017), findings revealed that neuroticism only influence the motivations behind Facebook usage and not directly affect the time being sent on Facebook. Furthermore, Hughes, Rowe, Batey, and Lee (2012) concluded that although it has been revealed in their study that an individual's personality was related to Facebook usage, the correlations were not direct or significant as other research suggested as other factors such as motivation behind Facebook use, self-efficacy and intelligence could be influential.…”
Section: Discussionmentioning
confidence: 84%
“…This implies that the more depressed an individual is and the more fearful of missing out, the higher the tendency of getting addicted to Facebook. Scherr and Brunet (2017) likewise postulated that people with depression use Facebook to fulfill psychological and social needs such as the need for social contact and to seek relief by gaining social support from others (Ryan, 2015). With the nature of depression which involves social isolation or diminished social activities, and possible lack of energy or drive to participate in direct face to face social interactions (Lin et al, 2016), depressed individuals try to compensate for their unmet needs with online connectedness thru social media use (Przybylski, Weinstein, Ryan, & Rigby, 2009).…”
Section: Discussionmentioning
confidence: 99%